Defense sector human resources management as the forefront in Corona Virus Disease (Covid-19) pandemic response - Widana, I Dewa Ketut Kerta; Subiyanto, Adi; Bimo, Emanuel Ario (Technium Social Sciences Journal, 2021)
Corona Virus Disease (COVID-19) pandemic is an actual threat currently experienced throughout the world, including Indonesia. COVID-19 pandemic response must be seriously carried out due to its threats against the national defense system. At the forefront of COVID-19 pandemic response is human resources that play important role as national defense system components which capability need to be managed and developed in a continuous manner. Against the background, this research aims to analyze defense sector human resource capacity management and development in COVID-19 pandemic response in Indonesia. This research employed descriptive qualitative method using primary and secondary data. The results showed that the capability-based approach emphasizes "what we need to do" in dealing with the increasingly complex threats, and defense sector human resources capacity development and management are carried out through selection and knowledge development processes to influence attitudes and encourage behavior changes. The results further showed that as a defense sector component, The Indonesian Armed Forces (TNI) personnel possesses the required readiness and capabilities to carry out their tasks with 3,426 medical and non-medical qualification personnel who have been directly involved at the forefront role of COVID-19 pandemic response.